2018
DOI: 10.1002/jia2.25121
|View full text |Cite
|
Sign up to set email alerts
|

“I will leave the baby with my mother”: Long‐distance travel and follow‐up care among HIV‐positive pregnant and postpartum women in South Africa

Abstract: IntroductionIt is common in urban African settings for postpartum women to temporarily return to family in distant settings. We sought to explore mobility among peripartum HIV‐positive women to understand the timing and motivation of travel, particularly vis‐à‐vis delivery, and how it may affect healthcare access.MethodsUsing the same mobility measurements within three different studies, we examined long‐distance travel of mother and infant before and after delivery in three diverse clinics within greater Joha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…Health system barriers noted in this study such as limited and unprofessional providers at healthcare facilities, and long travel distance to care have been identified in other research [12,14,15,18]. This study reported some communities were up to 20 km away from the health facilities.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Health system barriers noted in this study such as limited and unprofessional providers at healthcare facilities, and long travel distance to care have been identified in other research [12,14,15,18]. This study reported some communities were up to 20 km away from the health facilities.…”
Section: Discussionsupporting
confidence: 49%
“…Health system barriers consist of structural, process, and relational issues. Shortages in healthcare personnel [12,14,17], long distance to health facilities [4,11,15,18] and poor interactions with patients are commonly reported barriers to HIV care [5,11,12,14]. Other health systems barriers have included frequent appointments [11,19,20], unfriendly health staff with a breakdown of patient-provider trust [5,7,11,14], and poor reimbursement for services by government and other financial support programs [9,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa's population is highly mobile; the most typical pattern is of circular, within-border migration between rural and urban areas, with the mobile individual keeping strong ties to the rural areas by sending remittances to their family and returning to the rural area for holidays and family events, and upon retirement, illness, or during lapses in employment [26]. Postpartum women in South Africa are likely to be a particularly mobile group, due to a tradition of returning to one's rural home after delivery to receive care from family members [12,[27][28][29]. Our recent formative work at three sites in Johannesburg found that among 150 peripartum, HIV-positive women interviewed, 44% planned to travel around delivery -typically after delivery -to stay with family, sometimes leaving the infant in the care of family while the mother returned to work in Johannesburg [29].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Postpartum women in South Africa are likely to be a particularly mobile group, due to a tradition of returning to one's rural home after delivery to receive care from family members [12,[27][28][29]. Our recent formative work at three sites in Johannesburg found that among 150 peripartum, HIV-positive women interviewed, 44% planned to travel around delivery -typically after delivery -to stay with family, sometimes leaving the infant in the care of family while the mother returned to work in Johannesburg [29]. With unlinked medical records and no way of tracking mobility, it is difficult to intervene appropriately to ensure continuity of HIV care for mother and infant.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Two articles in this volume examine women's migration in the context of pregnancy. Clouse and colleagues present findings from a mixed methods study to identify drivers and types of mobility among pregnant and postpartum women living with HIV in the Johannesburg area in South Africa. They examine long‐distance travel of mothers and infants before and after delivery, finding that the frequent mobility in the peripartum period “underscores the challenge of ensuring a continuity of HIV care in a fragmented health care system that is not adapted for a mobile population.” In another setting in South Africa (Cape Town), Phillips and colleagues also examined the mobility of women attending an integrated antenatal‐ART clinic.…”
mentioning
confidence: 99%